Evaluation of the simulator with automatic irrigation control system designed for countermeasures of internal contamination in dental unit water lines. Issue 6 (June 2020) - Okubo, Keisuke; Ito, Takashi; Okamoto, Kentaro; Yamamoto, Ichiro; Mizutani, Hajime; Kawata, Yusuke; Shiota, Yasuyoshi; Ito, Masahiro; Nakamura, Shin; Tai, Masako; Yamamoto, Tadashi; Takashiba, Shogo
Abstract: The prevention of nosocomial infections is an imperative task. The dental chair unit (DCU) is an indispensable device used in dental treatment. However, it is known that the dental unit water line (DUWL) can become contaminated with biofilm, consisting mainly of heterotrophic bacteria (HB). Recently, the International Organization for Standardization specified the methods for testing DUWL contamination management. On these grounds, a simulator reproducing DUWL was prepared to standardize the examination method of the DUWL contamination. Objectives: To evaluate the reproducibility of the DUWL simulator, monitor the DUWL contamination states, and test the efficacy of a commercial decontaminant for DUWL. Methods: The DUWL simulator was assembled by a DCU manufacturing company. The simulator's DUWL was filled with tap water (TW), and left for approximately one year. Neutral electrolyzed water (NEW) was used as a decontaminant for DUWL. Both TW and NEW were passed through DUWL in a timely manner simulating daily dental treatment. Water was sampled from the air turbine hand piece weekly for 4 weeks and used for HB culture. Contamination status was evaluated by measuring bacterial adenosine triphosphate release and by culturing on Reasoner's 2A medium. Results: The DUWL released contaminated water had a bacterial count of over 6 × 10 4 cfu/mL. After passing NEW through DUWL for 1 week, the count drastically decreased to its basal level and remained steady for 4 weeks. However, TW showed no effect on DUWL decontamination throughout the examination periods. Conclusions: The DUWL simulator could be useful to examine the efficacy of the decontaminant for DUWL and development of new methods in DUWL contamination management. Abstract : Microbiology; Biomedical devices; Safety engineering; Microorganism; Biofilms; Dentistry; Dental chair unit water line (DUWL); Automated simulator; Water decontamination.